Reforma al artículo 434 del código del trabajo, respecto al número de trabajadores que exige el ministerio del trabajo, para que el empleador este obligado a elaborar el reglamento de higiene y seguridad - Díaz Gonzáles, Johanness Marlon (2017)
Ecuador is a Constitutional State of Rights and Justice, guarantor of rights and constitutional guarantees. Whose main characteristic is the submission of the law to the existing constitutional order. One of the most important rights in our Constitution is the right to work, which we guarantee in all its forms whether as employees or independently. This recognition would be empty if the state would not guarantee working people full respect for their dignity, decent living wages and fair remuneration and performance of a healthy work freely chosen or accepted. The right to health is a right inherent to the work, whose realization is linked to the exercise of other rights, including the right to water, food, education, physical culture, work, social security, healthy environments and others that support good living. Likewise, the right to social security is an inalienable right to work without these rights can not speak of a decent job. Our Constitution defines work as a right and a social duty, and an economic right, a source of personal fulfillment and base of the economy. Therefore the state is responsible workers to perform their work within any area in enjoyment of their constitutional rights. Safety and hygiene in the workplace are fundamental axes for a good performance of workers and benefits for employers, if the rights are put at risk violent labor and family welfare of workers. The Labour Code regulates the relationship between workers and employers, particularly in its Art. 434, establishes a number of ten workers, employers are required to prepare and submit for approval by the Ministry of Labour and Employment through the Regional Directorate of worker, health and safety regulations, the same that will be renewed every two years. This dissipation is discriminatory, violates the rights of workers because the employer does not comply with this requirement not hire more staff, denying the opportunity to work. In addition, a number less than ten would not enjoy a health and safety regulations. Therefore legal reform by the National Assembly is required to comprehensively respect the rights of workers.